Key technologies development and application prospect of ROADM all-optical switching network - Kai LV; Bin QI; Shengqian ZHONG; Anxu ZHANG; Lipeng FENG (Dianxin kexue)
The development history of reconfigurable optical add/drop multiplexer (ROADM) networks, ROADM technical solutions and the deployment of ROADM networks in China were described.And the development direction of the key technologies of ROADM was described, including optical cross-connect (OXC), high dimensions wavelength selected switch (WSS), colorless/directionless/contentionless ROADM (CDC-ROADM), 400 Gbit/s FlexGrid ROADM, and next-generation wavelength switched optical networks (WSON2.0) intelligent control plane technologies.The existing ROADM network application scenarios and technology development trend were analyzed, and the future prospects of the ROADM all-optical switching network were looked forward to.